Организация лабораторных практикумов по изучению аппаратно-элементной базы с применением виртуальных измерителей - Письменецкий, В. А.; Шокало, В. М.; Семенец, В. В. (УАДО, 2002)
The problems of organizing laboratory practical works directed to studying the mam parameters of the modem element base as well as basic functional nodes and modules of the modem radio electronic systems are considered.
Keywords: виртуальные измерители; организация лабораторных практикумов